TINJAUAN YURIDIS PENERAPAN PRINSIP KEHATI-HATIAN TERHADAP KEGIATAN USAHA PERBANKAN KHUSUS PENYALURAN KREDIT TANPA AGUNAN UNTUK APARATUR SIPIL NEGARA - Indah Palupi Utaminingtyas; Tomi Suryo Utomo (Universitas Janabadra, 2022)
Abstract: The objectives of this study are: 1) To identify and analyze the application of the precautionary principle to banking business activities specifically for the distribution of Unsecured Loans for State Civil Apparatus at Bank Sleman; 2) To find out and analyze the opportunities for State Civil Apparatus in applying for Unsecured Loans compared to other customers at Bank Sleman; and 3) To identify and analyze the obstacles faced in the application of the prudential principle to banking business activities specifically for the distribution of Unsecured Loans for State Civil Apparatus at Bank Sleman.This research is an empirical normative legal research using a law approach and a case approach. The nature of this research is descriptive. This research was conducted at the Sleman Bank Office with the resource person Yunisfi Ekasari R as HRD Manager of PT. BPR Bank Sleman (Perseroda). The author uses primary data and secondary data. The secondary data used consists of primary, secondary, and non-legal materials. The data collection technique was carried out in 2 stages, namely Interview, and Document Study. The data analysis technique in this study was carried out by means of qualitative data analysis.The results showed that the implementation of prudence implemented by Bank Sleman was by verifying at the time of initial submission and monitoring every month in the form of invoices taken through the treasurer of insurance that covers life and Termination of Employment (PHK). The chance of passing the application for Unsecured Credit at Bank Sleman is the same between State Civil Apparatus and non-State Civil Apparatus. The obstacle that often occurs in the provision of unsecured loans is the problem of bad loans. Bank Sleman overcomes these obstacles by verifying and always confirming the treasurer and periodically monitoring related to collective invoices